Fulfillment of Simple Proof Requirements on Bankruptcy Application Based on Sema Number 03 of 2023 - Widhayaka, Unggul Wibawa; Retnaningsih, Sonyendah; Ramadhan, Muhammad Rizqi Alfarizi (KRTHA BHAYANGKARA, 2025)
The Supreme Court has issued Circular Letter Number (SEMA) 3 of 2023 which stipulates that simple proof cannot be applied in bankruptcy against apartment and/or flat developers. The circular is predicted to protect consumer interests and eliminate legal remedies in the form of bankruptcy applications to the commercial court, so that they must be submitted as lawsuits to the district court. The circular is not in accordance with the principle of integration in Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (KPKPU Law). The KPKPU Law has clearly defined the matter of simple proof, and does not provide special protection for apartment and/or flat developers. Normative research is carried out with doctrinal research and tests the level of synchronization of regulations. The research is evaluative, examining cases that have occurred, based on comparative law. From this study it is concluded that proof is categorized as simple if there is a debt that is due and unpaid and there are two or more creditors. The requirement for simple proof does not consider the complexity of its impact on consumers. SEMA is a policy regulation, so if it conflicts with the regulations above it, the principle of lex superior derogat legi inferiori will apply. SEMA 03 of 2023 cannot change the provisions of the law, so simple proof can still be implemented against apartment developers. SEMA 03 of 2023 is not in line with the KPKPU Law so that by law it should be cancelled.